CRITICAL REVIEW ON A DISCOURSE ANALYSIS RESEARCH: WHAT NOVICE WRITERS CAN LEARN - Aldha Williyan; Sirniawati Sirniawati; Tia Nur Istianah; Mochamad Guntur (English Review: Journal of English Education, 2023)
EFL learners inevitably will enter the world of academia, which makes it mandatory for them to write academic writings, especially in the form of research articles. They are obliged to broaden knowledge in the field of their interest by conducting research. Unfortunately, academic writing has always been a serious challenge for them. Writing research articles indeed requires them to be familiar with the writing guidelines, particularly about how the ideas are developed. This present study is therefore intended to assist EFL learners, particularly those who have just started their academic writing experience. Insight and ideas on how to write a research article are presented in this paper. To do that, a qualitative methodology on discourse analysis was employed. The data was taken from a research article focusing on discourse marker comparisons between academic and non-academic writings. The article is broken down in detail to provide a clear picture of how it is constructed by the authors. The analysis revealed that even though it contains some minor weaknesses, the research article overall is well-written and follows the author guidelines. This study allows EFL learners to receive more explicit input and, hopefully, adapt and adopt the steps of how the article is written.